Fill in the blanks (B1, B2, B3) in the equation based on the graph.(a-B1)2 + (y-B2)² = (B3)²8182=83=Blank 1:
![Fill in the blanks B1 B2 B3 in the equation based on the graphaB12 yB2 B3818283Blank 1 class=](https://us-static.z-dn.net/files/d5b/612515cd00b00b4fdfb52b76a172ff4c.png)
Given: a circle is given with center (3,-3) and equation
[tex](x-B_1)^2+(y-B_2)^2=(B_3)^2[/tex]Find:
[tex]B_{1,\text{ }}B_{2,}B_3[/tex]Explanation: the general equation of the circle with center (a,b) and radius r is
[tex](x-a)^2+(y-b)^2=r^2[/tex]in the given figure the center of the circle is at (3,-3)
so the equatio of the circle becomes
[tex](x-3)^2+(y+3)^2=(3)^2[/tex]on comparing eith the given equation we get
[tex]B_1=3,\text{ B}_2=-3\text{ and B}_3=3[/tex]